IDEAL DAN ELEMEN IDEMPOTEN PADA RING DERET PANGKAT TERGENERALISASI - , SITI MUANAH; , Dr. Budi Surodjo, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this final project, we discuss about ideal I1 of Generalized Power Series Rings (GPSR) which is constructed from ideal I of commutative ring R with identity. We also discuss about ideal I2 of GPSR which is constructed from radical of ideal I and radical of ideal I1 of GPSR. Moreover, we discuss about idempotents of GPSR and its characteristics.